The Hundred Differences between Islamic and Conventional Banking Systems - Basha, S Nayamath (International Journal of Scientific Research and Management (IJSRM), 2017)
Islamic Banking is a catchphrase now to many of the policy makers in the globe. Neither receipt norpayment of interest in this system questions its survival. Astoundingly, it has proved itself as a moreeffective system than currently practiced interest based banking system. However, the recent globaleconomic crisis has impacted financial performance of many banks all over the world. It has forced around123 banks in the U.S. to file for bankruptcy in just a year, including American giant bank LehmanBrothers that was never been expected to fail. Fascinatingly, even in such turmoil Islamic banks are foundto be relatively less affected by the crisis than their conventional peers (S E Hidayat et al, 2012).Consequently, a lot of interest is shown by the economists across the world in assessing its feasibility inadapting in main stream economy. In this context, an attempt is made in this paper to understand thedifferences between Islamic and conventional banking systems in practices and their impact on economicvariables such as inflation, full employment, exports, business cycles etc.